1982
DOI: 10.1677/joe.0.0950071
|View full text |Cite
|
Sign up to set email alerts
|

The origin of cortisol in the blood of fetal sheep

Abstract: The blood clearance rate (BCR) of cortisol was measured in non-pregnant ewes and in pregnant ewes and their intact or bilaterally adrenalectomized fetuses. In pregnant sheep the placental transfer of cortisol in both directions was established. The BCR of cortisol in the non-pregnant sheep was 51.7 +2- 4.9 (S.E.M.) l/h (n = 36) or 1.15 l/h per kg body weight. This was lower than that in the pregnant ewe (97-143 days of gestation) of 76.9 +/- 4.21 l/h (n = 9) or 1.85 l/h per kg. In the intact fetus the BCR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 24 publications
(43 reference statements)
6
49
1
Order By: Relevance
“…There was a highly significant correlation between GFR and amount of sodium reabsorbed in both proximal and distal segments. The gradient These were well within the range of values previously reported in this laboratory (19).…”
Section: Resultssupporting
confidence: 90%
“…There was a highly significant correlation between GFR and amount of sodium reabsorbed in both proximal and distal segments. The gradient These were well within the range of values previously reported in this laboratory (19).…”
Section: Resultssupporting
confidence: 90%
“…These findings are consistent with previous studies that showed reduced placental 11 -HSD2 gene expression in sheep and rats during conditions such as maternal undernutrition which raise glucocorticoid concentrations in utero (Langley-Evans et al 1996, Bertram et al 2001. Indeed, cortisol-induced downregulation of placental 11 -HSD2 activity could explain, at least in part, the lower transplacental passage of cortisol from ewe to fetus observed during late gestation when fetal cortisol levels are reduced by fetal adrenalectomy (Hennessy et al 1982). In contrast to the placenta, cortisol administration had no effect on 11 -HSD2 activity in fetal ovine kidneys.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the fetuses were not instrumented, and therefore fetal plasma concentrations of ACTH and cortisol were not measured, as it is not possible to chronically instrument fetuses before mid-gestation. However, cortisol in fetal sheep comes almost entirely from the mother before GD 122 (Hennessy et al, 1982), and therefore, maternal elevations in cortisol as observed in this study would result in some degree of cortisol elevation in the fetus. These elevations may permanently alter the development and function of the HPA axis, and thus lead to long-term behavioral, cognitive, and immune deficits (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
“…Cortisol readily crosses the placenta and maternal cortisol is the chief source of cortisol in the ovine fetus until gestational day 121 (term is 147 days), following which 12 to 40% is derived from the mother (Beitins et al, 1970;Hennessy et al, 1982). Further, alterations in fetal cortisol concentrations by alcohol may also impact on fetal thyroid hormone concentrations (Forhead et al, 2006).…”
Section: Introductionmentioning
confidence: 99%